Unleashing potential: the talent pool management practices of UiTM Library / Azizi Jantan and Nurul Aida Noor Azizi - Jantan, Azizi; Noor Azizi, Nurul Aida (2023)
Libraries now recognize the immense value of collective expertise and the importance of cultivating a culture of continuous learning and knowledge sharing. They are embracing new strategies to maximize the potential of their staff's talents, harnessing them for the greater benefit of the library and its patrons. This article delves into the ten subject areas within the Talent Pool program, shedding light on their respective initial phases, talent selection facilitation, monitoring mechanisms, and the best practices employed to cultivate Subject Matter Experts (SMEs). By delving into these areas, the article aims to showcase how the UiTM Library effectively develops and nurtures experts who can make invaluable contributions to both the library itself and the broader academic community. This article aims to shed light on the extraordinary talents reside within the walls of libraries, showcasing the diverse abilities of the staff members who go above and beyond their traditional roles. From welcoming smiles at the front desk to the behind-the-scenes wizards curating collections and designing innovative programs, libraries are home to an ensemble of talented individuals.